Optical dating of late Quaternary carbonate sequences of Saurashtra, western India. Issue 1 (6th February 2017) - Sharma, Komal; Bhatt, Nilesh; Shukla, Anil Dutt; Cheong, Dae-Kyo; Singhvi, Ashok Kumar
Abstract: Bioclastic carbonate deposits that formed because of a combination of nearshore marine, fluvial, and aeolian processes, occur along the Saurashtra coast and in the adjacent interior regions of western India. Whether these carbonates formed by marine or aeolian processes has been debated for many decades. The presence of these deposits inland poses questions as to whether they are climate controlled or attributable to postdepositional tectonic uplift. In particular, the debate centres on chronologic issues including (1) appropriate sampling strategies and (2) the use of 230 Th/ 234 U and 14 C ages on the bulk carbonates. Using traces (<1%) of quartz grains trapped in carbonate matrices, optically stimulated luminescence (OSL) dating of quartz grains, deposited along with the carbonate grains, provides ages for the most recent deposition events. The OSL ages range from >165 to 44 ka for the shell limestones, 75–17 ka for the fluvially reworked sheet deposits, and 80–11 ka for miliolites deposited by aeolian processes. These are younger than the 230 Th/ 234 U and 14 C ages and suggest that the inland carbonate deposits were reworked from older carbonate sediments that were transported during more arid phases.